Revealing the relative importance among plant species, slope positions, and soil types on rhizosphere microbial communities in northern tropical karst and non-karst seasonal rainforests of China - Zhang, Xingming; Wang, Bin; Chen, Ting; Guo, Yili; Li, Xiankun (Frontiers in Microbiology, 2023)
Rhizosphere microbes have an extremely close relationship with plants and the study on the relationship between rhizosphere microorganisms and their influencing factors is conducive to the protection of vegetation and the maintenance of biodiversity. Here we investigated how plant species, slope positions and soil types affect the rhizosphere microbial community. Slope positions and soil types were collected from northern tropical karst and non-karst seasonal rainforests. The results indicated that soil types played a predominant role in the development of rhizosphere microbial communities (28.3% of separate contribution rate), more than plant species identity (10.9% of separate contribution rate) and slope position (3.5% of separate contribution rate). Notably, environmental factors closely related to soil properties were the major influence factors that controlling the rhizosphere bacterial community structure in the northern tropical seasonal rainforest, especially pH. Additionally, plant species also influenced the rhizosphere bacterial community. In low nitrogen content soil environments, rhizosphere biomarkers of dominant plant species were often nitrogen-fixing strains. It suggested that plants might have a selective adaptation mechanism to rhizosphere microorganisms to obtain the advantages of nutrient supply. Overall, soil types exerted the biggest influence on rhizosphere microbial community structure, followed by plant species and finally slope positions.